Bound spin-excitons in two-dimensional electron gas: Статьи, посвященные столетию со дня рождения Л. В. Шубникова - Fleurov, V.; Kikoin, K. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
A theory of the spin exciton capture by a magnetic impurity in a 2D electron gas is developed. Weconsider a resonance model for the electron scattering by a transition metal impurity and calculate the binding potential for spin excitons. This potential is spin selective and is capable of binding a spin exciton with zero angular momentum. In order to trap an exciton with a nonzero angular momentum m, the potential must exceed a certain threshold value, depending on m.